2017
DOI: 10.18203/2394-6040.ijcmph20171796
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks of measles in Rajasthan in 2014: a cross sectional epidemiological investigation

Abstract: Background: In India, although the measles vaccine is available across the country up to village level, but still India is struggling with mortality and morbidity associated with Measles and its outbreaks.  Investigations in measles outbreak help to know the determinants behind it and thus prevent further outbreaks. The outbreaks of measles in Rajasthan were investigated in 2014 by analyzing various socio-demographic parameters. Objective: To assess the epidemiological profile of measles outbreak in Rajasthan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…The low vaccine coverage could have increased the susceptibility of children and adults for measles infection. Similar findings of low vaccine coverage being associated with measles outbreaks were observed in different parts of India 7,8 , Nepal 9 , Bangladesh 10,11 , Sri Lanka 12,13 , Thailand 14 and Lao PDR 14 .…”
Section: Discussionsupporting
confidence: 80%
“…The low vaccine coverage could have increased the susceptibility of children and adults for measles infection. Similar findings of low vaccine coverage being associated with measles outbreaks were observed in different parts of India 7,8 , Nepal 9 , Bangladesh 10,11 , Sri Lanka 12,13 , Thailand 14 and Lao PDR 14 .…”
Section: Discussionsupporting
confidence: 80%
“…This findings were similar to a study conducted by Singh et al where the incidence of disease was highest among unimmunized children followed by partially immunized followed by completely immunized. 10 In the present study, the most common complication was diarrhea (20.5%) followed by pneumonia (13.3%) and around 11.3% of them developed otitis media. The present study findings were similar to a study by Deepa et al and Rahima et al 7,8 This findings differed to a study by sultana et al, where pneumonia was the most common complication (63.6%).…”
Section: Discussionsupporting
confidence: 47%
“…7 The present study findings were different in comparison to a study conducted in Rajasthan where 60% of study subjects were females. 10 In the present study, almost half the cases (49.2%) were reported in the months of October-December (corresponding to winter season). The present study findings concurred with a study conducted by Babita et al where maximum cases were found in the months of September to December.…”
Section: Discussionsupporting
confidence: 47%
“…The WHO estimated the coverage of first-dose vaccine in South-east Asia (which includes India) to be below the levels that would achieve herd immunity (85% in 2012) and stagnation of coverage in the past decade (Dabbagh et al, 2017; Moss, 2017). Documented measles outbreaks indicate that India remains endemic to measles given suboptimal coverage, with about 3 million infants not receiving first-dose measles vaccination in 2013 (Dabbagh et al, 2017; Jamir et al, 2016; Singh and Garg, 2017; Vaidya et al, 2016). India’s Integrated Disease Surveillance Program reported a decline in annual measles outbreaks during 2011–2013 but gradual increases since (Ministry of Health and Family Welfare, 2018).…”
Section: Discussionmentioning
confidence: 99%